Intraoperative radiation therapy (IORT) in head and neck cancer: A systematic review. Issue 50 (December 2016) - Kyrgias, George; Hajiioannou, Jiannis; Tolia, Maria; Kouloulias, Vassilios; Lachanas, Vasileios; Skoulakis, Charalambos; Skarlatos, Ioannis; Rapidis, Alexandros; Bizakis, Ioannis
Abstract: Background: Multimodality therapy constitutes the standard treatment of advanced and recurrent head and neck cancer. Since locoregional recurrence comprises a major obstacle in attaining cure, the role of intraoperative radiation therapy (IORT) as an add-on in improving survival and local control of the disease has been investigated. IORT allows delivery of a single tumoricidal dose of radiation to areas of potential residual microscopic disease while minimizing doses to normal tissues. Advantages of IORT include the conformal delivery of a large dose of radiation in an exposed and precisely defined tumor bed, minimizing the risk of a geographic miss creating the potential for subsequent dose reduction of external beam radiation therapy (EBRT). This strategy allows for shortening overall treatment time and dose escalation. The aim of this review is to summarize recent published work on the use of IORT as an adjuvant modality to treat common head and neck cancer in the primary or recurrent setting. Methods: We searched the Medline, Scopus, Ovid, Cochrane, Embase, and ISI Web of Science databases for articles published from 1980 up to March 2016. Results: Based on relevant publications it appears that including IORT in the multimodal treatment may contribute to improved local control. However, the benefit in overall survival is not so clear. Conclusion: IORT seems to be a safe, promising adjunct in the management of head and neck cancer and yet further well organized clinical trials are required to determine its role more precisely.